THE IMPACT OF GOOD CORPORATE GOVERNANCE AND ORGANIZATIONAL CULTURE ON PERFORMANCE AS MEDIATED BY JOB SATISFACTION - Susanto, Yohanes; Rimbano, Dhe (ITB AAS Indonesia Surakarta, 2024)
This study aims to examine the company's status following the Covid pandemic and the potential strategic actions to affect employee performance. By gathering actual data from respondents, researchers can evaluate the viability of the put out hypotheses using inference verification procedures. 115 research samples in total were purposefully chosen to participate as responders. We utilize Smart PLS software 3.29 to analyze structural equation models. The results of the study are: (1) Good corporate governance has an influence on job satisfaction; (2) organizational culture has an influence on job satisfaction; (3) Good corporate governance has an influence on performance, (4) Organizational culture has an influence on performance, (5) Job satisfaction has an influence on performance, (6) Job satisfaction mediates good corporate governance on performance and (7) Job satisfaction mediates the influence of organizational culture on performance. A limitation of this study is that the survey only focused on Palembang city area companies Practical implications: from the research indicate that in order to improve performance, new techniques must first boost employee job satisfaction. Performance is influenced by organizational culture, which is the second most important factor. By increasing both internal and external satisfaction, one can increase job satisfaction. (1) Team culture, which is a workplace culture that promotes interpersonal, collaborative, and communicative work environments, can improve organizational culture. aims to establish a business that is like a happy, large family, (3) Adaptive culture, particularly the culture present in an organization or company where employee changes occur, including how the company maintains and maintains the work environment, (2) mission culture, which is a stable and external culture that emphasizes the organization with clear goals and variables, as well as the process of continuous internal improvement and (4) bureaucratic culture, i.e. internal and stable culture for a highly effective organization with a high level of consistency in all its activities. This research examines the performance of regional companies after the occurrence of Covid-19 which is related to the impact of good corporate government and organizational culture which are rarely studied on the sustainability of the performance of regional companies in Indonesia.